Fibrillar structures induced by a plant reovirus target mitochondria to activate typical apoptotic response and promote viral infection in insect vectors. - Qian Chen; Limin Zheng; Qianzhuo Mao; Jiejie Liu; Haitao Wang; Dongsheng Jia; Hongyan Chen; Wei Wu; Taiyun Wei (PLoS Pathogens, 2019)
Numerous plant viruses that cause significant agricultural problems are persistently transmitted by insect vectors. We wanted to see if apoptosis was involved in viral infection process in the vector. We found that a plant reovirus (rice gall dwarf virus, RGDV) induced typical apoptotic response during viral replication in the leafhopper vector and cultured vector cells, as demonstrated by mitochondrial degeneration and membrane potential decrease. Fibrillar structures formed by nonstructural protein Pns11 of RGDV targeted the outer membrane of mitochondria, likely by interaction with an apoptosis-related mitochondrial protein in virus-infected leafhopper cells or nonvector insect cells. Such association of virus-induced fibrillar structures with mitochondria clearly led to mitochondrial degeneration and membrane potential decrease, suggesting that RGDV Pns11 was the inducer of apoptotic response in insect vectors. A caspase inhibitor treatment and knockdown of caspase gene expression using RNA interference each reduced apoptosis and viral accumulation, while the knockdown of gene expression for the inhibitor of apoptosis protein improved apoptosis and viral accumulation. Thus, RGDV exploited caspase-dependent apoptotic response to promote viral infection in insect vectors. For the first time, we directly confirmed that a nonstructural protein encoded by a persistent plant virus can induce the typical apoptotic response to benefit viral transmission by insect vectors.